The Workaholism Phenomenon in Portugal: Dimensions and Relations with Workplace Spirituality - Mónico, Lisete S. (2021)
Workaholism phenomenon affects a quarter of the employed world population. The concept has been used to describe hardworking employees, which is not resulting from external requirements. Considering that organizations with well-developed workplace spirituality have employees more committed to achieving self-development, but also to serve the company, the relationship between workaholism and workplace spirituality is not straightforward, remaining unclear. The principal aim of this research is to analyze the workaholism phenomenon, considering patterns of workaholic and non-workaholic workers and their relationships with dimensions of workplace spirituality. The sample is comprised of a heterogeneous group of 306 Portuguese employees, who were surveyed by theWorkaholism Battery, five dimensions ofWorkplace Spirituality, and a sociodemographic questionnaire. Cluster analysis defined three workaholic profiles (24% of the sample), and five non-workaholic profiles. Workplace spirituality dimensions differed according to worker profile and associations with work involvement, work enjoyment, and compulsive work addiction. Enthusiastic addicts and work enthusiasts showed the highest workplace spirituality, contrasting mainly with Reluctant hard worker, Disenchanted workers, and Unengaged workers, but also with work addicts. Workaholism is a complex and multidimensional phenomenon, whose dimensions are distinctly related to workplace spirituality. Workplace spirituality development can promote a more balanced and healthy relationship with work.